Antibodies to neutrophil cytoplasmic antigens in Wegener's granulomatosis and other conditions. Issue 5 (May 1989) - Harrison, D J; Simpson, R; Kharbanda, R; Abernethy, V E; Nimmo, G
Abstract : The use of serum antibodies to neutrophil cytoplasmic antigens (ANCA) as a diagnostic marker for Wegener's granulomatosis and other forms of vasculitis has been assessed. Although ANCA have been described by several groups the precise antigenic targets are unknown, and detection of ANCA still relies on an indirect immunofluorescence assay technique. Several different patterns of fluorescence have been produced by using sera from different groups of patients, and insufficient information is available on the frequency of positive results and of the patterns of immunofluorescence obtained when serum from patients with vasculitis as a part of a generalised connective tissue disease is used. A study was carried out on serum from 240 patients, including 23 patients with Wegener's granulomatosis, 12 with microscopic polyarteritis, and 30 with various connective tissue diseases. Three patterns of fluorescence were observed: bright coarsely granular cytoplasmic, bright non-granular cytoplasmic, and weak diffuse cytoplasmic. The bright, coarsely granular pattern was 86% specific for Wegener's granulomatosis in this series and was observed in 18 of 23 cases. Other patterns of fluorescence were found in various conditions and were not of diagnostic value. The technique is simple, inexpensive, rapid, and reproducible.